Challenges in postnatal care provision in Ethiopia - Bala, Elias Teferi; Roets, Lizeth (Frontiers in Public Health, 2022)
Background Most maternal deaths occur during the first 48 h after delivery; thus, a critical time for monitoring possible complications arising from the delivery. Quality postnatal care can contribute to a decrease in maternal mortality and morbidity rates. Despite the importance of postnatal care, it is generally a neglected aspect of maternal and child health services in most developing countries, including Ethiopia. Objectives The objective of the study was to describe the challenges experienced by postnatal care providers and coordinators in providing postnatal care in the Ethiopian context. Methods A quantitative cross-sectional descriptive study was conducted and data were gathered from 422 postnatal care providers and coordinators during November 2018. A simple random sampling technique was used to select the respondents and the data were gathered through a self-administered questionnaire. The data were cleaned, coded and entered into the Statistical Package for Social Sciences (SPSS) version 21 for analysis. Open-ended questions for qualitative enhancement were open-coded and thematically analyzed. Results The findings revealed a lack of physical resources; infrastructure problems; cultural concerns; inadequate capacity building; inaccessibility of health services; unavailability of guidelines; a lack of communication with healthcare users and poor monitoring and evaluation as challenges. Conclusion To improve postnatal care in Ethiopia and, ultimately, mother and child health, the challenges experienced by postnatal care providers and coordinators have to be dealt with. A strategic action plan with the active involvement of all stakeholders must be developed and implemented to deal with the challenges and improve postnatal care.